Three‐Dimensional Printing of Elastomeric, Cellular Architectures with Negative Stiffness. (2nd May 2014) - Duoss, Eric B.; Weisgraber, Todd H.; Hearon, Keith; Zhu, Cheng; Small, Ward; Metz, Thomas R.; Vericella, John J.; Barth, Holly D.; Kuntz, Joshua D.; Maxwell, Robert S.; Spadaccini, Christopher M.; Wilson, Thomas S.
<x xml:space="preserve">Abstract</x> Three‐dimensional printing of viscoelastic inks to create porous, elastomeric architectures with mechanical properties governed by the ordered arrangement of their sub‐millimeter struts is reported. Two layouts are patterned, one resembling a "simple cubic" (SC)‐like structure and another akin to a "face‐centered tetragonal" (FCT) configuration. These structures exhibit markedly distinct load response with directionally dependent behavior, including negative stiffness. More broadly, these findings suggest the ability to independently tailor mechanical response in cellular solids via micro‐architected design. Such ordered materials may one day replace random foams in mechanical energy absorption applications.